Generation and characterization of an improved carbon fiber model by molecular dynamics. (March 2021) - Shi, Linyuan; Sessim, Marina; Tonks, Michael R.; Phillpot, Simon R.
Abstract: A high-fidelity model is necessary for understanding the properties of carbon fibers (CFs) and developing the next generation of CFs and related composites. Using kinetic Monte Carlo combined with large-scale Molecular Dynamics (kMC-MD), we generate two types of CF models at a wide range of initial densities (from 1.2 g/cm 3 to 2.0 g/cm 3 ). These fiber core and thin fiber models represent a small section of interior region of large fiber and a very thin carbon fiber with a well-defined surface, respectively. The microstructures of the fiber core and thin fiber are characterized in terms of their shapes, densities, pore size distribution and hybridization of carbon atoms. We find both the fiber core and thin fiber models have densities and structural characteristics similar to experimental structures. Further, the virtual X-ray diffraction profiles shows good agreement with experimental profiles. In addition, more realistic CF models based on fiber core and thin fiber structure are proposed by removing layers of carbon atoms at random positions of each graphitic sheet along the longitudinal axis. Analysis shows that a fraction of the artificial introduced defects is healed during structural equilibration and the Young's moduli of these models, obtained from axial tensile simulations, are in the experimental range. Graphical abstract: Image 1